2011
DOI: 10.1139/e11-006
|View full text |Cite
|
Sign up to set email alerts
|

Crustal velocity structure of the southern Nechako basin, British Columbia, from wide-angle seismic traveltime inversion1This article is one of a series of papers published in this Special Issue on the theme of New insights in Cordilleran Intermontane geoscience: reducing exploration risk in the mountain pine beetle-affected area, British Columbia.

Abstract: In the BATHOLITHSonland seismic project, a refraction – wide-angle reflection survey was shot in 2009 across the Coast Mountains and Interior Plateau of central British Columbia. Part of the seismic profile crossed the Nechako Basin, a Jurassic–Cretaceous basin with potential for hydrocarbons within sedimentary strata that underlies widespread volcanic rocks. Along this 205 km-long line segment, eight large explosive shots were fired into 980 seismometers. Forward and inverse modelling of the traveltime data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…In a velocity-depth function from the Batholiths profile (Fig. 2) representative of the Chilcotin plateau (Stephenson et al 2011), the velocity gradient increases at ϳ18 km depth where the velocity is 6.35 km/s, resulting in a velocity increase from 6.45 to 6.9 km/s through the reflective lower crust (Fig. 8).…”
Section: Crustal-scale Extensionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a velocity-depth function from the Batholiths profile (Fig. 2) representative of the Chilcotin plateau (Stephenson et al 2011), the velocity gradient increases at ϳ18 km depth where the velocity is 6.35 km/s, resulting in a velocity increase from 6.45 to 6.9 km/s through the reflective lower crust (Fig. 8).…”
Section: Crustal-scale Extensionmentioning
confidence: 99%
“…In the southern Cordillera, although there is some variation in crustal thickness within the two belts, seismic reflection and refraction data show that the Moho increases in depth eastward from 32 to 37 km beneath the Omineca belt (Cook et al 1992;Clowes et al 1995). Just south of the 2008 Geoscience BC reflection survey, a seismic refraction survey indicates that the crustal thickness in the Chilcotin plateau is 34-36 km (Stephenson et al 2011). Thus, beneath Cartoon showing crustal extension accommodated by block faulting above a network of anastomosing shear zones in the middle crust that sole out into the top of the lower crust (after Allmendinger et al 1987).…”
Section: Comparison With Lithoprobe Transectsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously identified basement ridges from shoaling of the 5.0 and 5.5 km/s isovelocity contours, but recognize that the actual depth to the top of the igneous basement could be in error by up to ϳ500 m when using the 5.5 km/s contour due to the small velocity contrast between low porosity sedimentary rocks and volcanic rocks at depths of ϳ 2 km. In their interpretation of a crustal-scale refraction survey, Stephenson et al (2011) suggested that the 5.0 km/s isovelocity contour indicated the base of the sedimentary units, and that the deeper 5.6 km/s isovelocity contour marked the crystalline basement beneath interbedded sedimentary and volcanic rocks.…”
Section: Comparison With Sonic Logsmentioning
confidence: 99%
“…For example, the modelling of refraction data (Stephenson et al 2011) across the central portion of our array (near stations THMB and RAMB; see fig. 2 of Stephenson et al 2011) suggests that the thickest surface sediments along the refraction line are about 4-5 km thick ( fig. 11 of Stephenson et al 2011), in good agreement with our results at the nearby stations THMB and RAMB (4.2-4.9 km thick).…”
Section: Comparison With Previous Geophysical Studiesmentioning
confidence: 99%